MONEY PAYMENT SYSTEM ADMINISTRATION COURSE IN ENGLISH COURSE ARYA INSTITUTIONS USING MICROSOFT VISUAL BASIC 6.0 - Herry Widiatmoko; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Scientific research is aimed to present monthly reports to the head of the institution by using Microsoft Visual Basic 6.0. This research is a scientific research by collecting data - data. Authors obtained data with observation. From this research we can conclude that by using computerized will gain the ease and speed up the process penbayaran.